Lay HIV counselors' knowledge and attitudes toward depression: A mixed-methods cross-sectional study at primary healthcare centers in Mozambique - Mandlate, Flavio; Greene, M. Claire; Pereira, Luis F.; Sweetland, Annika C.; Kokonya, Donald; Duarte, Cristiane S.; Cournos, Francine; Oquendo, Maria A.; Wainberg, Milton L.; Sidat, Mohsin; Sevene, Esperança; Mello, Marcelo F. (Frontiers in Public Health, 2022)
Introduction Depression is the most common mental disorder among people living with HIV/AIDS and has a negative impact on HIV treatment outcomes. Training lay HIV counselors to identify and manage depression may contribute to improved patient access and adherence to treatment, and reduce stigma and discrimination among lay health workers toward both HIV and depression. The purpose of this study was to assess the current knowledge and attitudes of lay HIV counselors toward managing depression in primary care in Mozambique. Methods We conducted a mixed-methods cross-sectional study to assess depression-related knowledge and attitudes among lay HIV counselors in 13 primary healthcare facilities in Mozambique. We used the quantitative Depression Attitude Questionnaire (DAQ) scale, followed by open-ended questions to further explore three key DAQ domains: the nature of depression, treatment preferences, and professional attitudes or reactions. Results The sample included 107 participants (77.6% female, mean age: 32.3 years, sd = 7.4). Most (82.2%) had less than a high/technical school education. Findings suggested that some HIV counselors had knowledge of depression and described it as a cluster of psychological symptoms (e.g., deep sadness, anguish, apathy, isolation, and low self-esteem) sometimes leading to suicidal thoughts, or as a consequence of life stressors such as loss of a loved one, abuse, unemployment or physical illness, including being diagnosed with HIV infection. HIV counselors identified talking to trusted people about their problems, including family and/or counseling with a psychotherapist, as the best way for patients to deal with depression. While acknowledging challenges, counselors found working with patients with depression to be rewarding. Conclusion Lay health counselors identified HIV and psychosocial issues as key risk factors for depression. They believed that the treatment approach should focus on social support and psychotherapy.